TRAINING ISLAM DAN BUDAYA LOKAL: TAFSIR QS AL-BAQARAH:177 DALAM GAGASAN PRIBUMISASI ISLAM ABDURRAHMAN WAHID DI HIMPUNAN MAHASISWA YAYASAN AL-KAHFI - Kholilurrohman Kholilurrohman; Nur Fitriana; Amira Fauziah; Sunarto Sunarto; Aldomi Putra; Enok Ghosiyah (MADANI Abdimas : Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
This study explores the integration of universal Islamic values with local culture through an analysis of the interpretation of QS Al-Baqarah verse 177 within the framework of Islamic indigenization (pribumisasi Islam) as conceptualized by Abdurrahman Wahid (Gus Dur). The verse is chosen for its emphasis on the principles of al-birr (righteousness), which encompasses not only theological aspects but also social and humanistic dimensions. Using a qualitative approach through literature review, this research examines how Gus Dur interprets righteousness as concrete social action and how he articulates these values within the pluralistic context of Indonesian society. The findings indicate that Gus Dur views QS Al-Baqarah:177 as theological justification for the integration of Islamic teachings and local culture, where values such as justice, equality, and solidarity with the marginalized serve as the foundation of social ethic